2022
DOI: 10.3390/pr10030560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Residual Compressive Strength of Tunnel Lining Concrete Structure after Fire Damage Based on Ultrasonic Pulse Velocity and Shear-Wave Tomography

Abstract: In this study, ultrasonic pulse velocity (UPV) and ultrasonic shear-wave tomography are combined to measure the residual compressive strength (RCS) of small-scale lining concrete blocks and to detect inner defects in the lining structure. The characteristics of and variations in the RCS of test blocks after being exposed to elevated temperatures (200–800 °C) and constant heating times (2 h, 3 h, and 4 h) were studied. At 800 °C, the RCS values reduced by 64.4%, 69.2%, and 74.6% at heating times of 2 h, 3 h, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This method can visualize the interior of the structure, but the IR temperature field photography technology is not sensitive enough and is highly dependent on temperature differences [7]. UI involves using the sound waves reflected from the surface of a medium to detect internal defects [8]. However, during the detection process, the transducer needs to be well coupled to the surface of the structure, which reduces its efficiency and applicability in tunnel detection [9].…”
Section: Introductionmentioning
confidence: 99%
“…This method can visualize the interior of the structure, but the IR temperature field photography technology is not sensitive enough and is highly dependent on temperature differences [7]. UI involves using the sound waves reflected from the surface of a medium to detect internal defects [8]. However, during the detection process, the transducer needs to be well coupled to the surface of the structure, which reduces its efficiency and applicability in tunnel detection [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel linings can sufer heavy structural damage or even collapse when exposed to tunnel fre temperature curves. Previous studies showed that tunnel fre temperature curve is diferent from normal temperature curve [17,18]. An assessment of postfre damage is the most important thing when evaluating the structural safety of a tunnel's concrete lining [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that tunnel fre temperature curve is diferent from normal temperature curve [17,18]. An assessment of postfre damage is the most important thing when evaluating the structural safety of a tunnel's concrete lining [17]. Wang et al [17] studied the residual compressive strength (RCS) of small-scale lining concrete blocks and detection of inner defects in the lining structure through combined ultrasonic pulse velocity (UPV) and ultrasonic shear-wave tomography.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations